Method for producing non-aqueous dispersion and laminate

JP7635715B2Active Publication Date: 2025-02-26AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021552435
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-18
Filing Date
2020-10-15
Publication Date
2025-02-26
Estimated Expiration
2040-10-15

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、分散安定性に優れ取扱性が良好であり、加工性に優れる成形品を形成可能な非水系分散液が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635715000001
    Figure 0007635715000001
  • Figure 0007635715000002
    Figure 0007635715000002
Patent Text Reader

Abstract

[Problem] To provide: a non-aqueous dispersion liquid which has good dispersion stability, and from which a molded product having excellent processability can be formed; and a method for producing a laminate using such a non-aqueous dispersion liquid. [Solution] A non-aqueous dispersion liquid according to the present invention includes: a first powder which is a polymer having a unit based on tetrafluoroethylene and a unit based on perfluoro(alkyl vinyl ether); a second powder which is polytetrafluoroethylene having a number average molecular weight of 10,000-200,000 as calculated by a predetermined formula; a nonionic surfactant; and a non-aqueous solvent. In addition, the percentage of the polytetrafluoroethylene with respect to the sum of the polymer and the polytetrafluoroethylene is preferably at most 50 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous dispersion containing a specific powder, and a method for producing a laminate using the non-aqueous dispersion. [Background technology]

[0002] A non-aqueous dispersion containing polytetrafluoroethylene (PTFE) powder is known as a material for forming molded products such as electrical insulating layers with excellent insulating properties (see Patent Document 1). However, since PTFE has poor adhesive properties with other materials, it is difficult to adhere molded products formed from the non-aqueous dispersion to other members when used. Furthermore, due to its characteristics, PTFE is highly susceptible to fiber formation, a process known as fibrillation, when subjected to shear force. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2016 / 159102 Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have found that when the non-aqueous dispersion is mixed with other materials (filler, varnish, etc.) and stirred, or when the amount of PTFE in the non-aqueous dispersion is increased to form a thick molded product, etc., this phenomenon is likely to occur significantly, making handling difficult. In addition, it was found that molded articles formed from non-aqueous dispersions also had problems with processability, such as the observation of PTFE aggregates, difficulty in fine processing when processed with a blade, drill, laser, etc., and residual lint. Furthermore, it was also found that such problems are likely to cause a decrease in reliability in the subsequent processing steps of the molded article.

[0005] As a result of extensive research, the present inventors have found that a non-aqueous dispersion using a combination of a specific tetrafluoroethylene polymer powder and a low molecular weight PTFE powder can solve these problems. The present invention is based on such findings, and aims to provide a non-aqueous dispersion that has excellent physical properties such as dispersion stability and coatability, and is easy to handle, and is capable of forming a molded product with excellent processability, and a method for producing a laminate using such a non-aqueous dispersion. [Means for solving the problem]

[0006] The present invention has the following aspects. <1> A non-aqueous dispersion liquid comprising: a first powder of a polymer having a unit based on tetrafluoroethylene and a unit based on perfluoro(alkyl vinyl ether); a second powder of polytetrafluoroethylene having a number average molecular weight of 10,000 to 200,000 as calculated based on the following formula (1); a nonionic surfactant; and a non-aqueous solvent. Mn = 2.1 × 10 10 ×ΔHc -5.16 ... (1) [In formula (1), Mn represents the number average molecular weight of the polytetrafluoroethylene, and ΔHc represents the heat of crystallization (cal / g) of the polytetrafluoroethylene measured by differential scanning calorimetry.] <2> The proportion of the polytetrafluoroethylene to the total of the polymer and the polytetrafluoroethylene is 50 mass% or less. <1> A non-aqueous dispersion of. <3> The proportion of powder having a particle size of 1 μm or less to the total powder dispersed in the non-aqueous dispersion liquid is 50% or less. <1> or <2> A non-aqueous dispersion of. <4> When the ratio of powder having a particle diameter of 1 μm or less to the total powder dispersed in the non-aqueous dispersion is X and the ratio of powder having a particle diameter of 10 μm or more is Y, Y / X is less than 0.05. <1> ~ <3> A non-aqueous dispersion of any one of the above. <5> The average particle size of the second powder is smaller than the average particle size of the first powder. <1> ~ <4> A non-aqueous dispersion of any one of the above. <6> The second powder has an average particle size of less than 1 μm, and the first powder has an average particle size of 1 μm or more. <1> ~ <5> A non-aqueous dispersion of any one of the above. <7> The non-aqueous solvent is an amide, a ketone or an ester. <1> ~ <6> A non-aqueous dispersion of any one of the above. <8> The non-aqueous solvent is N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone, or γ-butyrolactone. <1> ~ <7> A non-aqueous dispersion of any one of the above. <9> The nonionic surfactant is a nonionic acetylene-based surfactant, a nonionic silicone-based surfactant, or a nonionic fluorine-based surfactant. <1> ~ <8> A non-aqueous dispersion of any one of the above. <10> The nonionic surfactant is a nonionic surfactant having a hydroxyl group and an oxyalkylene group and having a static surface tension of 28 mN / m or less. <1> ~ <9> A non-aqueous dispersion of any one of the above. <11> In addition, the above-mentioned <1> ~ <10> A non-aqueous dispersion of any one of the above. <12> The above composition further contains an inorganic filler. <1> ~ <11> A non-aqueous dispersion of any one of the above. <13> the above <1> ~ <12> a non-aqueous dispersion of any one of the above-mentioned items is applied to a surface of a substrate, followed by heating to form a polymer layer, thereby obtaining a laminate having the substrate and the polymer layer in this order. Effect of the Invention

[0007] According to the present invention, a non-aqueous dispersion liquid which has excellent dispersion stability and good handleability and is capable of forming a molded article having excellent processability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The following terms have the following meanings. The "melt viscosity of polymer" is a value measured in accordance with ASTM D 1238 using a flow tester and a 2Φ-8L die, with a polymer sample (2 g) that had been heated at the measurement temperature in advance for 5 minutes being held at the measurement temperature under a load of 0.7 MPa. "Standard specific gravity of polymer" is a value measured in accordance with ASTM D 4895-04. The "melting temperature (melting point) of a polymer" is the temperature corresponding to the maximum value of the melting peak of the polymer as measured by differential scanning calorimetry (DSC). The "glass transition point of a polymer" is a value measured by analyzing a polymer using a dynamic mechanical analysis (DMA) method. "Average particle size of powder (D50)" is the cumulative 50% diameter on a volume basis of powder determined by laser diffraction / scattering method. In other words, the particle size distribution of powder is measured by laser diffraction / scattering method, and a cumulative curve is calculated with the total volume of the group of powder particles as 100%, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. "D90 of powder" is the volume-based cumulative 90% diameter of the powder measured in a similar manner.

[0009] The D50 and D90 of the first powder or the second powder are determined by dispersing the powder in a state (i.e., a dry state) before being used in the preparation of the non-aqueous dispersion in water and analyzing it with a laser diffraction / scattering type particle size distribution analyzer (LA-920, manufactured by Horiba, Ltd.). The D50 and D90 of all powders (first powder and second powder) present in the non-aqueous dispersion are determined by analyzing the non-aqueous dispersion with a laser diffraction / scattering type particle size distribution analyzer (LA-920, manufactured by Horiba, Ltd.). The "viscosity of the non-aqueous dispersion" is a value measured using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used. The "thixotropy ratio of a non-aqueous dispersion" is a value (η1 / η2) calculated by dividing the viscosity η1 measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm.

[0010] The "static surface tension of a surfactant" is determined by the Wilhelmy method using an automatic surface tensiometer CBVP-Z model (manufactured by Kyowa Interface Science Co., Ltd.) and a 0.1% by mass aqueous solution of the surfactant. "Dynamic surface tension of surfactant" refers to the dynamic surface tension of a 0.1% by mass aqueous solution of the surfactant at 25°C with a bubble generation period of 6 Hz according to the maximum bubble pressure method, and is the value measured by the maximum bubble pressure method in an environment of 25°C when the sensor of a dynamic surface tensiometer Theta T60 manufactured by Eiko Seiki Co., Ltd. is immersed in the aqueous solution containing 0.1% by mass of the surfactant. The measurement is performed with the bubble generation period of the aqueous solution set to 6 Hz. The "HLB value of a surfactant" is a value calculated using the Griffin formula, and is found by dividing the sum of the molecular weights of the hydrophilic parts in the molecule by the molecular weight of the surfactant and multiplying the result by 20. The "unit" in a polymer may be an atomic group formed directly from a monomer by a polymerization reaction, or may be an atomic group in which a part of the structure is converted by treating a polymer obtained by a polymerization reaction with a predetermined method. A unit based on monomer A contained in a polymer is also simply referred to as a "monomer A unit".

[0011] The non-aqueous dispersion of the present invention contains a first powder of a polymer having units based on tetrafluoroethylene (TFE) (TFE units) and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (hereinafter also referred to as a "PFA-based polymer"), a second powder of polytetrafluoroethylene (hereinafter also referred to as a "low molecular weight PTFE") having a number average molecular weight of 10,000 to 200,000 calculated based on the following formula (1), a nonionic surfactant, and a non-aqueous solvent. The number average molecular weight of the low-molecular-weight PTFE is a value calculated based on the following formula (1). Mn = 2.1 × 10 10 ×ΔHc -5.16 ... (1) In formula (1), Mn represents the number average molecular weight of the low-molecular-weight PTFE, and ΔHc represents the heat of crystallization (cal / g) of the low-molecular-weight PTFE measured by differential scanning calorimetry. It should be noted that the PFA-based polymer is a different polymer from low-molecular-weight PTFE.

[0012] The non-aqueous dispersion of the present invention is a dispersion in which a first powder and a second powder are dispersed. Low molecular weight PTFE has a certain heat of crystallization and low fibrillation. On the other hand, the powder (second powder) is not likely to settle and has a certain degree of dispersibility, but has very low strength and is brittle, so that the particle size is likely to fluctuate due to physical stress (shear, etc.) during dispersion processing or mixing processing with other materials, or due to changes over time. In contrast, the non-aqueous dispersion of the present invention contains a powder (first powder) of a PFA-based polymer. The PFA-based polymer can be said to be a crystalline polymer containing TFE units, and is likely to interact with low molecular weight PTFE, and the powder (first powder) is not easily affected by the above-mentioned stress or changes over time.

[0013] In the non-aqueous dispersion of the present invention, an interaction that can be considered a mild coagulation action occurs between the first powder and the second powder, and at least a portion of the two powders form pseudo-secondary particles. Therefore, it is considered that the stress resistance and temporal stability of the powder as a whole are improved. Furthermore, the non-aqueous dispersion of the present invention contains a nonionic surfactant that exhibits a high degree of dispersion action in a non-aqueous solvent. Therefore, even if such secondary particles are formed, it is considered that the dispersion stability is highly maintained. It is believed that due to such an action mechanism, the non-aqueous dispersion of the present invention has excellent dispersion stability, and the physical properties of the molded article (polymer layer, etc.) formed therefrom are improved.

[0014] Specifically, in the molded article formed from the non-aqueous dispersion of the present invention, the PFA-based polymer and the low molecular weight PTFE are easily uniformly dispersed. Therefore, the inherent physical properties of the low molecular weight PTFE (particularly, electrical properties such as low dielectric tangent) are easily expressed in the molded article. In addition, the properties of the PFA-based polymer that easily exhibit good adhesion to other substrates are also easily expressed in a high degree, and the molded article is easily improved in adhesion to other substrates. Furthermore, in molded products, the drawbacks of low molecular weight PTFE, such as poor mechanical properties such as toughness and poor processability, are easily compensated for by the PFA-based polymer, which has excellent physical properties. Conversely, the difficulty in processability due to the high toughness of the PFA-based polymer, for example, the generation of lint when drilling holes in a printed circuit board having a polymer layer as a molded product, is highly alleviated and suppressed by the inclusion of low molecular weight PTFE. For this reason, for example, when a printed circuit board having a polymer layer is produced as a molded product, the generation of lint during drilling or router processing is easily suppressed. As a result, the nonaqueous dispersion of the present invention is particularly useful as a material for producing a printed circuit board having excellent electrical properties (particularly low dielectric tangent) and high reliability of electrical connection with wiring, electronic components, etc.

[0015] The first powder in the present invention may contain components other than the PFA-based polymer, but is preferably composed only of the PFA-based polymer. The content of the PFA-based polymer in the first powder is preferably 80% by mass or more, and more preferably 100% by mass. Examples of components other than the PFA-based polymer include aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides. In addition to the PFA-based polymer, inorganic substances can also be mentioned. As inorganic substances, oxides, nitrides, metal elements, alloys and carbon are preferred, silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride and magnesium metasilicate (steatite) are more preferred, silica and boron nitride are even more preferred, and silica is particularly preferred. Such a first powder is likely to have improved dispersibility. The first powder containing an inorganic substance preferably has a PFA-based polymer as a core and has an inorganic substance on the surface of the core. Such a first powder can be obtained, for example, by bonding (collision, aggregation, etc.) a powder of a PFA-based polymer and a powder of an inorganic substance.

[0016] The D50 of the first powder is preferably less than 5 μm, and more preferably 3 μm or less.The D50 of the powder is preferably 0.1 μm or more, and more preferably 1 μm or more. Furthermore, the D90 of the powder is preferably 10 μm or less, and more preferably 6 μm or less. If the particle size of the first powder is within this range, not only will the fluidity and dispersibility be good, but the interaction with the second powder will be balanced, making it easier to improve the dispersion stability of the non-aqueous dispersion.

[0017] The first powder may be corona-treated, plasma-treated, electron-beam-treated, or radiation-treated. By introducing oxygen-containing polar groups (>C(O), -C(O)F, etc.) to the surface of the first powder by these treatments, the dispersibility of the first powder and the adhesion of the surface of the molded article (polymer layer) are more likely to be improved. In addition, the PFA-based polymer and the low-molecular-weight PTFE are more likely to interact with each other, and the interactions between the powders are more balanced, so that the dispersion stability of the non-aqueous dispersion is more likely to be improved. As a result, the physical properties such as electrical properties (particularly low dielectric tangent) and processability due to the low-molecular-weight PTFE are more likely to be significantly expressed in the molded article.

[0018] The second powder in the present invention may contain components other than the low-molecular-weight PTFE, but is preferably composed only of low-molecular-weight PTFE. The content of low-molecular-weight PTFE in the second powder is preferably 80% by mass or more, and more preferably 100% by mass. Examples of components other than low molecular weight PTFE include aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides. The second powder may contain an inorganic substance. Examples of the inorganic substance include the same inorganic substances as those that may be contained in the first powder. The second powder containing an inorganic substance preferably has a core of low molecular weight PTFE and has the inorganic substance on the surface of the core. Such a second powder is obtained, for example, by bonding (colliding, agglomerating, etc.) low molecular weight PTFE and powder of the inorganic substance.

[0019] The D50 of the second powder is preferably less than 1 μm, and more preferably 0.8 μm or less.The D50 of the second powder is preferably 0.01 μm or more, and more preferably 0.1 μm or more. The D90 of the second powder is preferably 6 μm or less, and more preferably 2 μm or less. If the particle size of the second powder is within this range, not only will the second powder have good fluidity and dispersibility, but the interaction with the first powder will be balanced, making it easier to improve the dispersion stability of the non-aqueous dispersion. The second powder is preferably sintered. In this case, the fluidity and dispersibility of the second powder are improved, and the interaction with the first powder is enhanced, which tends to improve the dispersion stability of the non-aqueous dispersion. As a result, the electrical properties (particularly low dielectric tangent) and physical properties such as processability due to the low molecular weight PTFE are easily manifested in the molded product.

[0020] In the present invention, the D50 of the second powder is preferably smaller than the D50 of the first powder. In this case, the interactions between the powders are more balanced, so that the dispersion stability of the non-aqueous dispersion is more likely to be improved. In addition, when producing a molded product, it is considered that the particles of the second powder fill the spaces between the particles of the first powder, so that the first powder and the second powder are packed more densely. Therefore, the obtained molded product is likely to exhibit the properties based on the PFA-based polymer and the properties based on PTFE well. Specifically, the D50 of the second powder is preferably less than 1 μm, and more preferably 0.1 to 0.8 μm, while the D50 of the first powder is preferably 1 μm or more, and more preferably 1 to 5 μm.

[0021] The particle size distribution of all the powders (the first powder and the second powder) in the nonaqueous dispersion of the present invention preferably exhibits a single peak. Moreover, the ratio of the powder having a particle size of 1 μm or less to the total powder is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less. In this case, if the D50 values ​​of the first powder and the second powder are within the above range, it is considered that the interaction between the first powder and the second powder is more appropriately expressed, and the dispersion stability of the non-aqueous dispersion is more likely to be improved. Therefore, the first powder and the second powder are easily packed sufficiently densely when producing a molded product.

[0022] Furthermore, when the percentage of the powder having a particle diameter of 1 μm or less in the total powder is X [%] and the percentage of the powder having a particle diameter of 10 μm or more is Y [%], Y / X (the value obtained by dividing Y by X) is preferably less than 0.05, more preferably less than 0.01. Y / X is preferably 0 or more. If Y / X is within this range, the proportion of powder with a particle size of 10 μm or more is small in the total powder. Due to the above-mentioned mechanism of action, the non-aqueous dispersion of the present invention not only easily forms such a state, but also easily maintains such a state even under physical stress. Therefore, it is easy to prevent the density of the molded product and the ratio of PFA-based polymer to PTFE from becoming uneven in each part of the molded product. As a result, the processability of the molded product is easily improved.

[0023] The PFA-based polymer in the present invention has TFE units and PAVE units. The melt viscosity of PFA-based polymer is 1×10 at 380℃. 2 ~1×10 6 Pa·s is preferred. The melting temperature (melting point) of the PFA polymer is preferably from 260 to 320°C, and more preferably from 285 to 320°C. The glass transition point of the PFA polymer is preferably from 75 to 125°C, and more preferably from 80 to 100°C. A PFA-based polymer having a melt viscosity, melting temperature, or glass transition point within the above range is more likely to interact with low-molecular-weight PTFE, and the interactions between the powders are more balanced, which makes it easier to improve the dispersion stability of the non-aqueous dispersion.

[0024] The PFA-based polymer preferably contains 90 to 99 mol % TFE units and 1 to 10 mol % PAVE units, and more preferably contains 95 to 98 mol % TFE units and 2 to 5 mol % PAVE units, based on all units constituting the polymer. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3, CF2=CFOCF2CF2CF3 (PPVE) or CF2=CFOCF2CF2CF2CF3, more preferably PPVE. PFA-based polymers in which the content of TFE units and PAVE units, or the type of PAVE, is within the above ranges are more likely to interact with low molecular weight PTFE, and the interactions between the powders are more balanced, which makes it easier to improve the dispersion stability of non-aqueous dispersions.

[0025] The PFA-based polymer may have units based on monomers other than the TFE unit and the PAVE unit. Examples of the monomer include olefins such as ethylene and propylene, fluoroolefins such as chlorotrifluoroethylene, hexafluoropropylene and fluoroalkylethylene, and monomers having an oxygen-containing polar group, which will be described later. Fluoroalkylethylenes include CH2=CH(CF2)2F, CH2=CH(CF2)4F, CH2=CF(CF2)2H, and CH2=CF(CF2)4H.

[0026] The PFA-based polymer preferably has an oxygen-containing polar group. The oxygen-containing polar group may be contained in the unit of the PFA-based polymer, or may be contained in the end group of the polymer main chain. The latter PFA-based polymer may include a PFA-based polymer having a polar functional group as an end group derived from a polymerization initiator, a chain transfer agent, etc., and a PFA-based polymer having an oxygen-containing polar group prepared by plasma treatment or ionizing radiation treatment. If the PFA-based polymer has an oxygen-containing polar group, the dispersibility of the first powder and the adhesion to the surface of the molded article are more likely to be improved. In addition, the PFA-based polymer and the low molecular weight PTFE are more likely to interact with each other, and the interactions between the powders are more balanced, so the dispersion stability of the non-aqueous dispersion is more likely to be improved. As a result, the electrical properties (particularly low dielectric tangent) and physical properties such as processability due to the low molecular weight PTFE are more likely to be significantly expressed in the molded article.

[0027] The oxygen-containing polar group is preferably a hydroxyl group-containing group, a carbonyl group-containing group, an acetal group or a phosphono group (-OP(O)OH2), and from the viewpoint of further improving the dispersion stability of the non-aqueous dispersion and the adhesion of the surface of the molded article, a hydroxyl group-containing group or a carbonyl group-containing group is more preferable, and a carbonyl group is even more preferable. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, and more preferably -CF2CH2OH, -C(CF3)2OH or a 1,2-glycol group (-CH(OH)CH2OH). The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-).

[0028] The PFA-based polymer having an oxygen-containing polar group preferably has a TFE unit, a PAVE unit and a unit based on a monomer having an oxygen-containing polar group. The monomer is preferably a monomer having a hydroxyl group-containing group or a carbonyl group-containing group, and more preferably a monomer having a carbonyl group-containing group. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride (also called himic anhydride; hereinafter also referred to as "NAH") or maleic anhydride, and more preferably NAH.

[0029] A preferred embodiment of the PFA-based polymer is a polymer containing 1 to 10 mol % of PAVE units based on all units, and is preferably a polymer (1) containing TFE units and PAVE units and having an oxygen-containing polar group, or a polymer (2) containing TFE units and PAVE units, containing 2 to 5 mol % of PAVE units based on all monomer units, and not having an oxygen-containing polar group, with polymer (1) being more preferred. Such a PFA-based polymer is in a state in which it is more likely to interact with the low-molecular-weight PTFE, and the interactions between the powders are more balanced, so that the dispersion stability of the non-aqueous dispersion is more likely to be improved.

[0030] The polymer (1) preferably contains 90 to 98 mol% of TFE units, 1 to 9.97 mol% of PAVE units, and 0.01 to 3 mol% of units based on a monomer having an oxygen-containing polar group, based on all units constituting the polymer. Specific examples of such PFA-based polymers include the polymers described in WO 2018 / 16644.

[0031] The polymer (2) is composed only of TFE units and PAVE units, and preferably contains 95 to 98 mol % of TFE units and 2 to 5 mol % of PAVE units based on the total monomer units. The content of the PAVE unit in the polymer (2) is preferably 2.1 mol % or more, more preferably 2.2 mol % or more, based on the total monomer units. In addition, the polymer (2) having no oxygen-containing polar group is 1×10 of the number of carbon atoms constituting the polymer main chain. 6 This means that the number of oxygen-containing polar groups in the polymer per unit is less than 500. The number of oxygen-containing polar groups is preferably 100 or less, and more preferably less than 50. The lower limit of the number of oxygen-containing polar groups is usually 0.

[0032] The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate an oxygen-containing polar group as a terminal group of the polymer chain, or by fluorinating an F polymer having an oxygen-containing polar group. As a method of fluorination, a method using fluorine gas (see JP 2019-194314 A, etc.) can be mentioned.

[0033] The low molecular weight PTFE in the present invention includes a homopolymer consisting of only TFE units, as well as a polymer containing a very small amount of units based on a monomer other than TFE in addition to TFE units. The latter polymer preferably contains 99.9 mol % or more of TFE units based on all units contained in the polymer. Examples of units other than TFE include units based on the above-mentioned olefins or the above-mentioned fluoroolefins.

[0034] The number average molecular weight of the low molecular weight PTFE is preferably 15,000 or more, more preferably 20,000 or more. The number average molecular weight of the low molecular weight PTFE is preferably 150,000 or less, more preferably less than 100,000. Low molecular weight PTFE powder has excellent dispersibility in non-aqueous dispersions, and because it exhibits thermal melting properties, it also has excellent moldability.

[0035] The standard specific gravity of the low molecular weight PTFE is preferably more than 2.15, and more preferably 2.17 to 2.25. PTFE with such a standard specific gravity indicates that it has a sufficiently low molecular weight. The melt viscosity of low molecular weight PTFE at 380℃ is 1×10 2 ~1×10 7 Pa s is preferred, 1×10 2 ~1×10 5 Pa·s is more preferred. PTFE having a standard specific gravity or melt viscosity within the above range indicates that it has a sufficiently low molecular weight. In addition, low molecular weight PTFE has a melt viscosity of 1×10 9It may be a low molecular weight PTFE obtained by irradiating a high molecular weight PTFE having a molecular weight of Pa·s or more with radiation, or it may be a low molecular weight PTFE obtained by using a chain transfer agent during the production.

[0036] The low molecular weight PTFE may also contain an oxygen-containing polar group at the end group of the polymer main chain. When the low molecular weight PTFE has an oxygen-containing polar group, the interaction with the nonionic surfactant is enhanced, the dispersibility in the non-aqueous dispersion is improved, and the molded article is likely to exhibit excellent adhesion to the substrate. Examples of the method for introducing the oxygen-containing polar group include a method of introducing the structure derived from the polymerization initiator, chain transfer agent, etc. used during production, and a method of introducing the PTFE by plasma treatment or ionizing radiation treatment. The oxygen-containing polar group is preferably a hydroxyl- or carbonyl-containing group as described above, and more preferably -CF2CH2OH or a carboxyl group (-COOH).

[0037] In addition, the low-molecular-weight PTFE preferably does not substantially contain a low-molecular-weight fluorine-containing compound having a polar group. Here, "substantially free of fluorine-containing compounds" means that the low-molecular-weight PTFE does not contain any of the fluorine-containing compounds, or the amount of the fluorine-containing compounds contained in the low-molecular-weight PTFE is on the order of "ppb". Specifically, the amount of the fluorine-containing compounds contained in the low-molecular-weight PTFE is preferably 30 ppb or less, more preferably 15 ppb or less, and even more preferably below the detection limit (5 ppb or less) in the measurement by the MRM (Multiple Reaction Monitoring) method.

[0038] The above fluorine-containing compound preferably has 6-40 carbon atoms, more preferably 6-25 carbon atoms, and even more preferably 8-14 carbon atoms. The polar groups of the above fluorine-containing compounds include carbonyl groups (>C(O)), sulfonyl groups (-SO2-), carboxyl groups (-COOH), carboxylate groups (-COO - NH4 + , -COO - Na +etc.), carboxyl derivatives (-CONH2 etc.), sulfo groups (-SO3H), sulfoxylate groups (-SO3 - Na + etc.), particularly, a carboxyl group, a carboxylate group, a sulfo group, and a sulfoxylate group.

[0039] Examples of the fluorine-containing compound include polyfluorocarbon-based fluorine-containing compounds such as polyfluorocarboxylic acids or salts thereof, and polyfluoroalcohols (eg, polyfluoroalkyl alcohols). Examples of the polyfluorocarboxylic acid include polyfluoroalkyl carboxylic acids such as polyfluorooctanoic acid, polyfluorodecanoic acid, polyfluorodecanoic acid, and polyfluorotetradecanoic acid. An ether oxygen atom may be inserted between carbon atoms of the polyfluoroalkyl carboxylic acid or polyfluoroalkyl alcohol.

[0040] The non-aqueous solvent in the present invention is preferably an aprotic polar compound that is inactive in liquid form at 25° C. and functions as a dispersion medium for the powder. Such a non-aqueous solvent is preferably a compound that has a lower boiling point and is more volatile than the components other than the non-aqueous solvent contained in the non-aqueous dispersion. The non-aqueous solvent may be used alone or in combination of two or more. The boiling point of the non-aqueous solvent is preferably 125 to 250° C. In this case, when the liquid coating of the non-aqueous dispersion of the present invention is dried to form a dry coating, the flow of the powder due to the evaporation of the solvent progresses effectively, and the powder is likely to be densely packed.

[0041] The non-aqueous solvent is preferably an amide, a ketone or an ester.Specific examples of the non-aqueous solvent include N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone, cyclopentanone, butyl acetate, methyl isopropyl ketone, cyclopentanone, and cyclohexanone, and N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone or γ-butyrolactone is preferred. A non-aqueous dispersion using such a non-aqueous solvent is likely to enhance the dispersing action of the nonionic surfactant and to improve the dispersion stability of the powder. As a result, the electrical properties (especially low dielectric tangent) and physical properties such as processability due to the low molecular weight PTFE are likely to be significantly expressed in the molded product.

[0042] The nonionic surfactant in the present invention preferably has a hydroxyl group (particularly an alcoholic hydroxyl group) or an oxyalkylene group (hereinafter also referred to as "AO group") as a hydrophilic site, and more preferably has an alcoholic hydroxyl group and an oxyalkylene group. Such a surfactant has improved affinity (interaction) with nonaqueous solvents via the AO group, and is likely to increase the dispersibility of the powder in the nonaqueous dispersion. The AO group may be composed of one kind of AO group, or may be composed of two or more kinds of AO groups. In the latter case, the different kinds of AO groups may be arranged randomly or in blocks. The AO group is preferably an oxyethylene group or an oxypropylene group, more preferably an oxyethylene group.

[0043] The nonionic surfactant preferably has an acetylene group-containing group, a polysiloxane group, a perfluoroalkyl group, or a perfluoroalkenyl group as a hydrophobic site, in other words, the nonionic surfactant is preferably a nonionic acetylene-based surfactant, a nonionic silicone-based surfactant, or a nonionic fluorine-based surfactant.

[0044] As the nonionic fluorine-based surfactant, a nonionic fluorine-based surfactant having a hydroxyl group (particularly, an alcoholic hydroxyl group), an AO group, and a perfluoroalkyl group or a perfluoroalkenyl group is preferred. Such surfactants have a high affinity with PFA-based polymers and PTFE, so the dispersion stability of the powder is more likely to be improved. As a result, the electrical properties (particularly, low dielectric tangent) and physical properties such as processability due to the low molecular weight PTFE are easily manifested in the molded product. The number of carbon atoms in the perfluoroalkyl group or the perfluoroalkenyl group is preferably from 4 to 16. In addition, an ether oxygen atom may be inserted between carbon atoms in the perfluoroalkyl group or the perfluoroalkenyl group.

[0045] The weight average molecular weight of the nonionic surfactant is preferably 1,000 to 80,000. The static surface tension of the nonionic surfactant is preferably 28 mN / m or less, more preferably 26 mN / m or less, and more preferably 15 mN / m or more, more preferably 20 mN / m or more. The dynamic surface tension of the nonionic surfactant is preferably 40 mN / m or less, more preferably 35 mN / m or less, and the dynamic surface tension is preferably 20 mN / m or more. When the static surface tension or dynamic surface tension of the surfactant is within this range, the non-aqueous dispersion tends to have excellent dispersion stability.

[0046] The HLB value of the nonionic surfactant is preferably 1 or more, more preferably 5 or more, and even more preferably 10 or more. The HLB value is preferably 18 or less, more preferably 16 or less, and even more preferably 15 or less. In this case, the nonaqueous dispersion tends to have excellent defoaming properties and dispersion stability.

[0047] The nonionic surfactant is preferably a nonionic surfactant having a hydroxyl group (particularly an alcoholic hydroxyl group) and an AO group, and having a static surface tension of 28 mN / m or less. The content of the AO group in the nonionic surfactant is preferably 10% by mass or more, more preferably 20% by mass or more. The AO content is preferably 50% by mass or less. In this case, the affinity of the nonionic surfactant to the nonaqueous solvent is further improved, and the dispersibility of the powder in the nonaqueous dispersion is likely to be further improved. When the nonionic surfactant has an alcoholic hydroxyl group, the hydroxyl value is preferably 100 mgKOH / g or less, more preferably 50 mgKOH / g or less. The lower limit of the hydroxyl value is preferably 10 mgKOH / g or more. When the nonionic surfactant is a nonionic fluorine-based surfactant, the fluorine content is more preferably from 20 to 50 mass %.

[0048] The nonionic fluorine-based surfactant is preferably a copolymer of a compound represented by the following formula (F) and a compound represented by the following formula (H). CH2=CHR F -C(O)OQ F -X F (F) CH2=CHR H -C(O)-(Q H ) m -OH (H) R F represents a hydrogen atom or a methyl group. Q F represents an alkylene group having 1 to 4 carbon atoms or an oxyalkylene group having 1 to 4 carbon atoms. X F represents a perfluoroalkyl group having 4 to 6 carbon atoms or a perfluoroalkenyl group having 4 to 12 carbon atoms. R H represents a hydrogen atom or a methyl group. Q H represents an oxyalkylene group having 2 to 4 carbon atoms. m represents an integer of 1 to 120.

[0049] The content of each compound contained in the copolymer may be appropriately determined depending on the type of each compound and the physical properties of the nonionic surfactant described above (fluorine content, AO group content, hydroxyl value, etc.). Specific examples of such nonionic surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan), and "KF-6011" and "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0050] Furthermore, the nonaqueous dispersion of the present invention may contain a resin other than the PFA-based polymer and PTFE, an inorganic filler, a thixotropy imparting agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a brightening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, or a flame retardant, as long as the effects of the present invention are not impaired. The viscosity of the non-aqueous dispersion of the present invention is preferably 10,000 mPa·s or less, and more preferably 10 to 1,000 mPa·s. The thixotropy ratio of the non-aqueous dispersion of the present invention is preferably 1-2. Due to the above-mentioned mechanism of action, the viscosity or thixotropy ratio of the non-aqueous dispersion of the present invention can be easily adjusted to fall within the above range.

[0051] In the present invention, the proportion of the low-molecular-weight PTFE to the total of the PFA-based polymer and the low-molecular-weight PTFE is preferably 50% by mass or less, and more preferably 40% by mass or less. The content (ratio) of the PFA polymer in the present invention is preferably from 10 to 45% by mass, more preferably from 15 to 40% by mass. The content (proportion) of the low-molecular-weight PTFE in the present invention is preferably from 5 to 40% by mass, more preferably from 10 to 35% by mass. When the above ratio, the content (ratio) of the PFA-based polymer, or the content (ratio) of the low molecular weight PTFE is within the above range, the interactions between the powders are easily balanced, and the dispersion stability of the non-aqueous dispersion is easily improved. Also, the obtained molded product is likely to exhibit a good balance of adhesion, electrical properties (particularly low dielectric tangent), and processability.

[0052] The content (proportion) of the non-aqueous solvent in the present invention is preferably from 10 to 85% by mass, more preferably from 20 to 75% by mass. The content (ratio) of the nonionic surfactant in the present invention is preferably from 1 to 15% by mass. When the content (ratio) of the non-aqueous solvent or the content (ratio) of the nonionic surfactant is within the above range, the powder is highly dispersible and the dispersion stability is easily improved.

[0053] The non-aqueous dispersion of the present invention is also excellent in mixability with resins other than the PFA-based polymer and low-molecular-weight PTFE (hereinafter also referred to as "other resins") and inorganic fillers. If the non-aqueous dispersion of the present invention contains other resins or inorganic fillers, it is easy to impart high physical properties based on the other resins or inorganic fillers to the molded article. The non-aqueous dispersion of the present invention preferably further contains another resin. In this case, in a molded article obtained from the non-aqueous dispersion, the other resin is uniformly dispersed, and the properties based on the other resin are likely to be exhibited well. The other resin may be a thermosetting resin or a thermoplastic resin. Examples of the other resins include epoxy resins, maleimide resins, urethane resins, elastomers, polyimides, polyamic acids, polyamideimides, polyphenylene ethers, polyphenylene oxides, and liquid crystal polyesters. For example, if aromatic polyimides are included as the other resins, good UV processability can be imparted to the molded product. When the non-aqueous dispersion contains another resin, it may be produced by mixing the non-aqueous dispersion of the present invention with a powder of the other resin, or by mixing the non-aqueous dispersion of the present invention with a varnish containing the other resin. The content of the other resin in the present invention is preferably from 0.1 to 40% by mass, and more preferably from 0.5 to 20% by mass.

[0054] The non-aqueous dispersion of the present invention preferably further contains an inorganic filler. In this case, in a molded article obtained from the non-aqueous dispersion, the inorganic filler is uniformly dispersed, and the properties based on the inorganic filler are likely to be exhibited well. The inorganic filler may be selected depending on the physical properties to be imparted to the molded article. Examples of inorganic fillers include nitride fillers and inorganic oxide fillers. Of these, preferred are silicate fillers such as boron nitride filler, beryllia (beryllium oxide), silica filler, wollastonite filler, and talc filler, or metal oxide fillers (cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), and more preferred is silica filler. The shape of the inorganic filler may be granular, non-granular (scale-like, layer-like), or fibrous, and it is preferable for it to have a fine structure. Specific examples of inorganic fillers having such a fine structure include spherical inorganic fillers and fibrous inorganic fillers. The average particle size of the former inorganic filler is preferably from 0.001 to 3 μm, and more preferably from 0.01 to 1 μm. In the latter inorganic filler, the length is the fiber length and the diameter is the fiber diameter. The fiber length is preferably 1 to 10 μm. The fiber diameter is more preferably 0.01 to 1 μm.

[0055] At least a portion of the surface of the inorganic filler may be surface-treated with an organic substance, an inorganic substance (however, the inorganic substance is different from the inorganic substance that forms the inorganic filler), or both. Examples of organic substances used in such coating treatments include polyhydric alcohols (trimethylolethane, pentaerythritol, propylene glycol, etc.), saturated fatty acids (stearic acid, lauric acid, etc.), their esters, alkanolamines, amines (trimethylamine, triethylamine, etc.), paraffin wax, silane coupling agents, silicones, and polysiloxanes. The inorganic substances used in such coating treatment include oxides, hydroxides, hydrated oxides, or phosphates of aluminum, silicon, zirconium, tin, titanium, antimony, and the like.

[0056] Specific examples of suitable inorganic fillers include silica fillers with an average particle size of 1 μm or less that have been surface-treated with an aminosilane coupling agent (such as the "Adma Fine" series manufactured by Admatechs Co., Ltd.), zinc oxide with an average particle size of 0.1 μm or less that has been surface-treated with an ester such as propylene glycol dicaprylate (such as the "FINEX" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica with an average particle size of 0.5 μm or less and a maximum particle size of less than 1 μm (such as the SFP grade manufactured by Denka Co., Ltd.), rutile-type titanium oxide with an average particle size of 0.5 μm or less that has been coated with a polyhydric alcohol and an inorganic substance (such as the "Tipaque" series manufactured by Ishihara Sangyo Kaisha, Ltd.), and alkyl silane fillers. Examples of fillers include rutile-type titanium dioxide having an average particle size of 0.1 μm or less that has been surface-treated with silane (such as the "JMT" series manufactured by Teika Corporation), hollow silica fillers (such as the "E-SPHERES" series manufactured by Taiheiyo Cement Corporation, the "Silinax" series manufactured by Nippon Steel Mining Co., Ltd., and the "Ecocospher" series manufactured by Emerson & Cumming Co., Ltd.), talc fillers (such as the "SG" series manufactured by Nippon Talc Co., Ltd.), steatite fillers (such as the "BST" series manufactured by Nippon Talc Co., Ltd.), and boron nitride fillers (such as the "UHP" series manufactured by Showa Denko KK, and the "Denka Boron Nitride" series ("GP" and "HGP" grades) manufactured by Denka Co., Ltd.).

[0057] The non-aqueous dispersion of the present invention can be applied to the surface of a substrate and heated to form a polymer layer, thereby producing a laminate having a substrate and a polymer layer in this order. In such a method (the present method), it is preferable to coat the surface of a substrate with a non-aqueous dispersion to form a liquid coating, heat and dry the non-aqueous dispersion, and then further bake the non-aqueous dispersion to form a polymer layer. The method for applying the non-aqueous dispersion in this method may be any method that can form a stable liquid coating on the surface of the substrate, and examples of such methods include spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, slot die coating, and comma coating.

[0058] The heating temperature (atmosphere temperature) when drying the liquid coating in this method may be set according to the melting temperatures of the low molecular weight PTFE and PFA-based polymers and the boiling point of the non-aqueous solvent, and is preferably 90 to 250°C, more preferably 100 to 200°C. The heating time is preferably from 0.1 to 10 minutes, and more preferably from 0.5 to 5 minutes. The heating in drying may be carried out in one stage, or in two or more stages at different temperatures. Furthermore, a portion of the non-aqueous solvent may remain in the dried coating.

[0059] The temperature (atmosphere temperature) when baking the dried coating in this method is equal to or higher than the melting temperature of the low-molecular-weight PTFE and may be set according to the type of low-molecular-weight PTFE, and is preferably 300 to 420°C, more preferably 320 to 400°C, and even more preferably 340 to 380°C. The heating time is preferably from 30 seconds to 5 minutes. Furthermore, the heating in the firing may be carried out in one stage, or in two or more stages at different temperatures.

[0060] The heating means for the drying and firing may be a method using a ventilated drying oven or a method using a heat ray irradiation oven such as infrared ray irradiation oven. The atmospheric state at that time may be either normal pressure or reduced pressure. The atmosphere in this case may be any of an oxidizing gas (oxygen gas, etc.) atmosphere, a reducing gas (hydrogen gas, etc.) atmosphere, and an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.), and from the viewpoint of suppressing alteration and deterioration of the polymer components contained in the nonaqueous dispersion liquid, an inert gas atmosphere is preferred.

[0061] The substrate in this method is preferably a metal foil or a heat-resistant resin film. The ten-point average roughness of the surface of the metal foil is preferably 5 μm or less, more preferably 1 μm or less. The ten-point average roughness of the surface of the metal foil is preferably 0.1 μm or more. In this case, the polymer layer and the metal foil are more strongly adhered to each other. For this reason, the dielectric loss tangent (Df) is more likely to decrease significantly in the laminate (polymer layer-coated metal foil) or in a printed circuit board obtained by processing the laminate. Specifically, when the substrate in this method is a metal foil, the dielectric loss tangent of the laminate at a frequency of 10 GHz is preferably 0.0015 or less, more preferably less than 0.001. The dielectric loss tangent is preferably 0.0001 or more. Examples of materials for the metal foil include copper, copper alloys, stainless steel, nickel, nickel alloys (including alloy 42), aluminum, aluminum alloys, titanium, and titanium alloys. The metal foil is preferably a rolled copper foil or an electrolytic copper foil.

[0062] The surface of the metal foil may be subjected to an anti-rust treatment (formation of an oxide film such as chromate). The surface of the metal foil may also be treated with a silane coupling agent. The treatment area may be a part of the surface of the metal foil or the entire surface. The thickness of the metal foil is preferably from 0.1 to 20 μm, and more preferably from 0.5 to 10 μm. The thickness of the polymer layer is preferably 1 to 20 μm, more preferably 2 to 18 μm, and further preferably 5 to 15 μm, in which case swelling of the interface between the polymer layer and the metal foil due to heating is suppressed and transmission loss in the high frequency range is significantly improved.

[0063] In addition, a carrier-attached metal foil containing two or more layers of metal foil may be used as the metal foil. Examples of carrier-attached metal foil include carrier-attached copper foils consisting of a carrier copper foil (thickness: 10 to 35 μm) and an ultra-thin copper foil (thickness: 2 to 5 μm) laminated on the carrier copper foil via a release layer. By using such carrier-attached copper foil, it is possible to form a fine pattern by the MSAP (modified semi-additive) process. A specific example of the metal foil with a carrier is "FUTF-5DAF-2" manufactured by Fukuda Metal Foil & Powder Co., Ltd.

[0064] The heat-resistant resin film may be a single-layer film or a multi-layer film. The heat-resistant resin film may have glass fibers, carbon fibers, or the like embedded therein. When the substrate is a heat-resistant resin film, it is preferable to form a polymer layer on both sides of the substrate. In this case, since the polymer layer is formed on both sides of the heat-resistant resin film, the linear expansion coefficient of the laminate is significantly reduced, and warping is unlikely to occur. Specifically, the absolute value of the linear expansion coefficient of the laminate in this embodiment is preferably 1 to 25 ppm / °C.

[0065] Examples of the heat-resistant resin include polyimide, polyarylate, polysulfone, polyarylsulfone, aromatic polyamide, aromatic polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, liquid crystal polyester, and liquid crystal polyesteramide, and polyimide (particularly, aromatic polyimide) is preferred. In the laminate which is a heat-resistant resin film having polymer layers on both sides, the thickness (total thickness) is preferably 25 μm or more, more preferably 50 μm or more, and is preferably 150 μm or less. In this configuration, the ratio of the total thickness of the two polymer layers to the thickness of the heat-resistant resin film is preferably 0.5 or more, more preferably 0.8 or more. The ratio is preferably 5 or less. In this case, the characteristics of the heat-resistant resin film (high yield strength, low plastic deformation property) and the characteristics of the polymer layer (low water absorption) are exhibited in a well-balanced manner.

[0066] A preferred embodiment of the laminate produced by this method, in which the substrate is a heat-resistant resin film, is a three-layer film in which the heat-resistant resin film is a polyimide film having a thickness of 20 to 100 μm, and a polymer layer, a polyimide film, and a polymer layer are laminated in this order in direct contact with each other. In this embodiment, the thicknesses of the two polymer layers are the same, and are preferably 15 to 50 μm. The ratio of the total thickness of the two polymer layers to the thickness of the polyimide film is preferably 0.5 to 5. The laminate of this embodiment is most likely to exhibit the effects of the laminate described above.

[0067] The outermost surface of the polymer layer of the laminate of the present invention may be further subjected to a surface treatment in order to further improve its linear expansion property and adhesiveness. Examples of the surface treatment method include annealing treatment, corona treatment, plasma treatment, ozone treatment, excimer treatment, and silane coupling treatment. The annealing conditions are preferably a temperature of 120 to 180° C., a pressure of 0.005 to 0.015 MPa, and a time of 30 to 120 minutes. Examples of gases used in the plasma treatment include oxygen gas, nitrogen gas, rare gas (such as argon), hydrogen gas, ammonia gas, and vinyl acetate. These gases may be used alone or in combination of two or more to form a mixed gas.

[0068] On the outermost surface of the polymer layer of the laminate of the present invention, another substrate may be further laminated. Other substrates include a heat-resistant resin film, a prepreg which is a precursor of a fiber-reinforced resin plate, a laminate having a heat-resistant resin film layer, and a laminate having a prepreg layer. Note that a prepreg is a sheet-like substrate in which a fiber base material (tow, woven fabric, etc.) of reinforcing fibers (glass fiber, carbon fiber, etc.) is impregnated with a thermosetting resin or a thermoplastic resin. The heat-resistant resin film may be the heat-resistant resin film described above.

[0069] As a method for lamination, a method of hot pressing the laminate and another substrate can be mentioned. When the other substrate is a prepreg, the heat press conditions are preferably a temperature of 120 to 300°C, a reduced atmospheric pressure (vacuum) of 20 kPa or less, and a press pressure of 0.2 to 10 MPa.When the other substrate is a heat-resistant resin film, the heat press conditions are preferably a temperature of 310 to 400°C. The laminate of the present invention has a polymer layer having excellent electrical properties (particularly, low dielectric tangent), and is therefore suitable as a printed circuit board material. Specifically, the laminate of the present invention can be used as a flexible metal-clad laminate or a rigid metal-clad laminate for the manufacture of printed circuit boards, and can be particularly suitable for use as a flexible metal-clad laminate for the manufacture of flexible printed circuit boards.

[0070] A printed circuit board is obtained by etching the metal foil of a laminate (polymer-layered metal foil) whose base material is metal foil to form a transmission circuit. Specifically, a printed circuit board can be manufactured by a method of processing a metal foil into a desired transmission circuit by etching the metal foil, or by a method of processing a metal foil into a desired transmission circuit by electrolytic plating (semi-additive method (SAP method), MSAP method, etc.). A printed circuit board manufactured from a polymer-layered metal foil has a transmission circuit formed from the metal foil and a polymer layer in this order. Specific examples of the configuration of a printed circuit board include transmission circuit / polymer layer / prepreg layer and transmission circuit / polymer layer / prepreg layer / polymer layer / transmission circuit. In the manufacture of such a printed circuit board, an interlayer insulating film may be formed on a transmission circuit, a solder resist may be laminated on the transmission circuit, or a coverlay film may be laminated on the transmission circuit. The nonaqueous dispersion of the present invention may be used as a material for these interlayer insulating films, solder resists, and coverlay films.

[0071] A specific embodiment of the printed board is a multi-layer printed circuit board in which the printed board is multi-layered. A preferred embodiment of the multilayer printed circuit board is one in which the outermost layer of the multilayer printed circuit board is a polymer layer, and the multilayer printed circuit board has one or more structures in which a metal foil or a transmission circuit, a polymer layer, and a prepreg layer are laminated in this order. The number of the above structures is preferably more than one (2 or more). A transmission circuit may be further disposed between the polymer layer and the prepreg layer. The multilayer printed circuit board of this embodiment has particularly excellent heat resistance and processability due to the outermost polymer layer. Specifically, even at 288°C, there is little interfacial swelling between the polymer layer and the prepreg layer, and little interfacial peeling between the metal foil (transmission circuit) and the polymer layer. In particular, even when the metal foil forms the transmission circuit, the polymer layer is firmly attached to the metal foil (transmission circuit), so warping is unlikely to occur and the heat resistance and processability are excellent.

[0072] A preferred embodiment of the multilayer printed circuit board is one in which the outermost layer of the multilayer printed circuit board is a prepreg layer, and the multilayer printed circuit board has one or more structures in which a metal foil or a transmission circuit, a polymer layer, and a prepreg layer are laminated in this order. The number of the above structures is preferably multiple (2 or more). A transmission circuit may be further disposed between the polymer layer and the prepreg layer. The multilayer printed circuit board of this embodiment has excellent heat resistance and processability even if it has a prepreg layer as the outermost layer. Specifically, even at 300°C, interfacial swelling between the polymer layer and the prepreg layer and interfacial peeling between the metal foil (transmission circuit) and the polymer layer are unlikely to occur. In particular, even if the metal foil forms the transmission circuit, the polymer layer is firmly attached to the metal foil (transmission circuit), so that warping is unlikely to occur and the heat resistance and processability are excellent. In other words, according to the present invention, printed circuit boards having various configurations can be easily obtained in which the respective interfaces are firmly adhered to each other without the need for various surface treatments, and in which the occurrence of interfacial blistering or interfacial peeling due to heating, particularly blistering or peeling in the outermost layer, is suppressed.

[0073] Although the nonaqueous dispersion and the method for producing the laminate of the present invention have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the nonaqueous dispersion of the present invention may additionally have any other constituent in the constitution of the above embodiment, or may be substituted with any constituent that produces a similar effect. Furthermore, the method for producing a laminate of the present invention may further include any other step in the configuration of the above embodiment, or may be substituted with any other step that produces a similar effect. EXAMPLES

[0074] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [powder] First powder 1: Powder (D50: 2 μm, D90: 5 μm) made of a polymer having an oxygen-containing polar group (melting temperature: 300°C) containing TFE units, NAH units, and PPVE units at 98.0 mol%, 0.1 mol%, and 1.9 mol%, respectively, in that order. First powder 2: Powder made of a polymer (melting temperature: 305°C) containing TFE units and PPVE units at 97.5 mol% and 2.5 mol% in that order and having no oxygen-containing polar group (D50: 4 μm, D90: 6 μm) · Second powder 1: Powder made of PTFE with Mn of 20,000 (D50: 0.6 μm, D90: 2 μm) Powder X: Powder made of PTFE with Mn of 1 million (D50: 0.8 μm, D90: 3 μm)

[0075] The Mn (number average molecular weight) of each PTFE was determined by analyzing the powder using a differential scanning calorimetry (DSC) device and measuring the heat of crystallization of the PTFE. That is, PTFE powder in a nitrogen atmosphere was heated to 400°C at a heating rate of 10°C / min, and then cooled to 200°C at a heating rate of 10°C / min. The area of ​​the DSC peak associated with crystallization observed near 320°C was calculated, and this was divided by the mass (10 mg) of the powder used in the measurement to obtain the heat of crystallization of PTFE. Based on this heat of crystallization of PTFE and the above formula (1), the Mn of PTFE was calculated.

[0076] [Non-aqueous solvent] ·NMP: N-methyl-2-pyrrolidone [Surfactants] ·Agent 1: CH2=C(CH3)C(O)OCH2CH2(CF2)6F and CH2=C(CH3)C(O)(OCH2CH2) 23 A nonionic surfactant that is a copolymer with OH, has an alcoholic hydroxyl group and an oxyalkylene group, and has a static surface tension of 25 mN / m (fluorine content: 35% by mass, oxyethylene group content: 34% by mass, hydroxyl value: 19 mgKOH / g) ·Agent 2: CH2=C(CH3)C(O)OCH2CH2(CF2)6F and CH2=C(CH3)C(O)(OCH2CH2) 66 A nonionic surfactant that is a copolymer with OCH3, has an oxyalkylene group, and has a static surface tension of 30 mN / m.

[0077] 1. Preparation of non-aqueous dispersion (Example 1) A solution was prepared in a pot by mixing NMP (45 parts by mass) and Agent 1 (5 parts by mass). A powder mixture of First Powder 1 (40 parts by mass) and Second Powder 1 (10 parts by mass) was added to this solution, zirconia balls were added, and the pot was rolled at 150 rpm for 1 hour to produce Non-aqueous Dispersion 1 in which First Powder 1 and Second Powder 2 were dispersed. (Examples 2 to 7) Non-aqueous dispersions 2 to 7 were obtained in the same manner as in Example 1, except that at least one of the type and amount of powder was changed. The compositions of the respective non-aqueous dispersions are shown in Table 1. The values ​​in Table 1 indicate the proportions (mass %) of each component in the non-aqueous dispersions.

[0078] [Table 1]

[0079] 2. Measurement and Evaluation 2-1. Measurement of the proportion of fine particles (powder with a particle size of 1 μm or less) The particle size of the powder dispersed in the non-aqueous dispersion liquid was measured by a laser diffraction / scattering method, and the percentage (%) of powder with a particle size of 1 μm or less was calculated. 2-2. Measurement of the ratio of coarse particles (powder with a particle size of 10 μm or more) The particle size of the powder dispersed in the non-aqueous dispersion liquid was measured by a laser diffraction / scattering method, and the proportion (%) of powder with a particle size of 10 μm or more in the total powder was determined, and the ratio of this to the proportion of the above-mentioned fine particles was calculated.

[0080] 2-3. Evaluation of dispersion stability The dispersion stability when 60 parts by mass of each non-aqueous dispersion and 40 parts by mass of aromatic polyimide varnish (solid content: 20% by mass, solvent: NMP) were mixed under shear treatment, and the dispersibility during re-dispersion treatment after long-term storage was evaluated according to the following criteria. ◯ (Good): Viscosity and foaming of the liquid are suppressed when mixed, and the liquid can be easily redispersed by simply stirring lightly even after long-term storage. △ (Fair): Viscosity increase of the liquid is suppressed when mixing, but foaming is likely. Shearing treatment is required for redispersion after long-term storage. × (Not acceptable): The liquid thickens significantly and foams violently when mixed. Redispersion after long-term storage requires shearing, which further thickens the liquid.

[0081] 2-4. Evaluation of coatability First, each non-aqueous dispersion was applied to the surface of the copper foil by a roll-to-roll die coating method to form a liquid coating. Then, the liquid-coated copper foil was passed through a drying oven at 140°C for 5 minutes and dried by heating. After that, the copper foil with the dry coating was transported so that the dry coating was in contact with 10 free rolls, and the presence or absence of powder falling off was visually confirmed just before the winding section, and evaluated according to the following criteria. ◯ (Good): No powder falling off was observed over the entire surface of the dried coating. △ (Fair): Powder falling off was observed in part (edge) of the dried coating. × (Fail): Powder loss was observed over the entire surface of the dry coating.

[0082] 2-5. Measurement of dielectric tangent Each of the copper foils with the dried coating obtained above was baked in a baking furnace at 350°C for 5 minutes under a nitrogen atmosphere to obtain a copper foil with a polymer layer (laminate).The copper foil was then etched with an aqueous ferric chloride solution to produce a single polymer layer, and the dielectric loss tangent at 10 GHz was measured by the SPDR (split post dielectric resonance) method. 2-6. Measurement of breaking elongation Each of the polymer layers obtained above was cut into a dumbbell shape (ASTM D638 type 5 shape), and the breaking elongation (%) between the benchmark lines was measured in a tensile test at a speed of 50 mm / min.

[0083] 2-7. Peel strength measurement First, each non-aqueous dispersion was applied to both sides of a 50 μm thick polyimide film (SKC Kolon PI, "FS-200") so that the resulting polymer layer had a thickness of 25 μm, and then dried at 140° C. for 5 minutes. Further, the film was baked at 380° C. for 10 minutes to prepare a polyimide film (laminate with a thickness of 100 μm) having polymer layers on both sides. Next, copper foil (manufactured by JX Metals Corporation, "BHM-102F-HA-V2") was placed on both sides of this laminate, and vacuum pressed at 350°C and 1 MPa for 20 minutes to obtain a double-sided copper-clad laminate. Then, unnecessary parts of the copper foil were etched away so that a 2 mm-wide strip remained, and the peel strength (N / cm) was measured when peeling this strip from the polymer layer at an angle of 90° at a speed of 50 mm / min, and this was taken as the peel strength.

[0084] 2-8. Evaluation of processability Each of the double-sided copper-clad laminates obtained above was subjected to drilling and plating as follows. In the drilling process, multiple through holes were formed, each of which had a shape in which two cylindrical through holes were connected by one rectangular through hole. The diameter of the cylindrical through hole was 0.4 mm, and the width of the rectangular through hole was 0.25 mm. For the drilling process, a drilling machine (manufactured by Via Mechanics, "ND-1S") equipped with a drill with a diameter of 0.2 mm was used, with the drill rotation speed set to 150,000 rpm and the feed speed set to 3 m / min.

[0085] Thereafter, the double-sided copper-clad laminate in which the through-holes had been formed was subjected to a permanganate treatment (desmear treatment), an electroless plating treatment, and an electrolytic plating treatment in this order. The permanganate treatment was carried out using the following chemical solutions (all manufactured by Atotech) under the following treatment conditions. Swelling treatment solution: Swelling Dip Securigant P (60°C for 6 minutes) Microetching solution: Concentrate Compact CP (10 minutes at 80°C) Neutralizing solution: Reduction Securigant P500 (40°C for 5 minutes)

[0086] The electroless copper plating process was carried out using the following chemical solutions (all manufactured by Uemura Kogyo Co., Ltd.) under the following processing conditions. Cleaning solution: MCD-PL (5 minutes at 40°C) Pre-dip solution: MDP-2 (2 minutes at 25°C) Activator solution: MAT-SP (40°C for 5 minutes) Reducer solution: MRD-2-C, MAB-4C and MAB-4A (35°C for 3 min) Accelerator solution: MEL-3-A (1 min at 25°C) Electroless copper plating solution: Thru-Cup PEA (20 minutes at 36°C)

[0087] The electrolytic copper plating process was carried out using the following chemicals so that the plated copper layer in the through-holes had a thickness of 20 μm. Acid cleaning solution: Acid cleaner FR (45°C for 5 minutes) Acid rinse: Sulfuric acid (1 minute at 23°C) Electrolytic copper plating solution: 23℃ After forming a plated copper layer in the through-hole, the electrical continuity between the plated copper layers in the two cylindrical through-holes was confirmed and evaluated according to the following criteria. ○(Good): Continuity × (Not possible): No continuity The results are summarized in the following Table 2. In the evaluation of the processability of Example 5, the polymer layer was found to be cracked.

[0088] [Table 2] [Industrial Applicability]

[0089] The non-aqueous dispersion of the present invention is excellent in dispersion stability, and can form a molded article (polymer layer) excellent in properties based on PFA-based polymers (adhesiveness, etc.) and properties based on PTFE (particularly electrical properties such as low dielectric tangent). In addition, a laminate obtained by using the non-aqueous dispersion of the present invention has excellent processability of the polymer layer, and is suitable as a printed circuit board material.

Claims

1. A non-aqueous dispersion comprising: a first powder of a polymer having a unit based on tetrafluoroethylene and a unit based on perfluoro(alkyl vinyl ether); a second powder of polytetrafluoroethylene having a number average molecular weight of 10,000 to 200,000 as calculated based on the following formula (1); a nonionic surfactant; and a non-aqueous solvent, wherein the second powder has an average particle size of less than 1 μm, the first powder has an average particle size of 1 μm or more, and the non-aqueous solvent is an amide, ketone, or ester. Mn = 2.1×10 10 ×ΔHc -5.16 ・・・ (1) [In formula (1), Mn represents the number average molecular weight of the polytetrafluoroethylene, and ΔHc represents the heat of crystallization (cal / g) of the polytetrafluoroethylene measured by differential scanning calorimetry.]

2. The nonaqueous dispersion according to claim 1 , wherein the proportion of said polytetrafluoroethylene with respect to the total of said polymer and said polytetrafluoroethylene is 50 mass % or less.

3. 3. The non-aqueous dispersion according to claim 1, wherein a ratio of powder having a particle size of 1 μm or less to all powder dispersed in the non-aqueous dispersion is 50% or less.

4. 4. The nonaqueous dispersion according to claim 1, wherein, when a ratio of powder having a particle diameter of 1 μm or less to all powders dispersed in the nonaqueous dispersion is X and a ratio of powder having a particle diameter of 10 μm or more is Y, Y / X is less than 0.

05.

5. The non-aqueous dispersion according to any one of claims 1 to 4, wherein the non-aqueous solvent is N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-pyrrolidone, or γ-butyrolactone.

6. The non-aqueous dispersion according to any one of claims 1 to 5, wherein the nonionic surfactant is a nonionic acetylene-based surfactant, a nonionic silicone-based surfactant, or a nonionic fluorine-based surfactant.

7. The non-aqueous dispersion according to any one of claims 1 to 6, wherein the nonionic surfactant has a hydroxyl group and an oxyalkylene group and has a static surface tension of 28 mN / m or less.

8. The non-aqueous dispersion according to any one of claims 1 to 7, further comprising another resin.

9. The non-aqueous dispersion according to any one of claims 1 to 8, further comprising an inorganic filler.

10. A method for producing a laminate, comprising applying the nonaqueous dispersion according to any one of claims 1 to 9 to a surface of a substrate, heating the resulting substrate, forming a polymer layer, and obtaining a laminate having the substrate and the polymer layer in this order.

Citation Information

Patent Citations

  • Fluororesin composition for part of electronic or electric equipment and part for electronic or electric equipment

    JP2000143921A

  • Curable resin composition, and flexible substrate and reflection sheet having film of curable resin composition

    JP2013067756A

  • Nonaqueous dispersion containing fluorine-based resin; polyimide precursor solution composition containing fluorine-based resin; polyimide, polyimide film and adhesive composition for circuit boards, each using said polyimide precursor solution composition containing fluorine-based resin; and production methods thereof

    WO2016159102A1

  • Liquid composition, and method for manufacturing film and layered body using same

    WO2018016644A1